Convergence or divergence? Decision-making during the Kennedy years. - Liaw, Wy Cin. (2008)
In this paper, I seek to challenge Lrving L. Janis’s thesis in groupthink in explaining decision-making during the Bay of Pigs operation, the failed covert U.S. paramilitary coup to overthrow the regime of Fidel Castro in Cube.